BRG1 regulates lipid metabolism in hepatocellular carcinoma through the PIK3AP1/PI3K/AKT pathway by mediating GLMP expression. Issue 5 (May 2022) - Liu, Gao; Sun, Bao-Ye; Sun, Jian; Zhou, Pei-Yun; Guan, Ruo-Yu; Zhou, Cheng; Yang, Zhang-Fu; Wang, Zhu-Tao; Zhou, Jian; Fan, Jia; Yi, Yong; Qiu, Shuang-Jian
Abstract: Background: Brahma-related gene 1 (BRG1) is essential for embryogenesis and cellular metabolism. A deficiency of BRG1 in vivo decreases lipid droplets, but the molecular mechanism underlying its role in lipid metabolism associated with hepatocellular carcinoma (HCC) remains unknown. Aims: We aimed to determine the role of BRG1 in lipid metabolism in HCC. Methods: We assessed the differential expression of BRG1 in HCC and adjacent non-tumorous tissues using tissue microarrays. We stained lipid droplets in HCC cells with Bodipy fluorescence and Oil Red O, and verified BRG1 binding to the promoter region of glycosylated lysosomal membrane protein (GLMP) using chromatin immunoprecipitation. Results: The expression of GLMP, a potential lipid metabolism regulator, was suppressed by BRG1 via transcriptional activity. Knockdown of BRG1 decreased lipid droplets, increased GLMP expression and altered the phosphoinositide-3-kinase adaptor protein 1 (PIK3AP1)/phosphatidylinositol-3 kinase (PI3K)/protein kinase B (AKT) pathway in HCC, which further GLMP knockdown partially restored. Thus, GLMP knockdown increased lipid droplets and differentially altered the PI3K/AKT pathway. Conclusions: Downregulating BRG1 decreased lipid droplet deposition in HCC cells by upregulating GLMP and altering the PI3K/AKT pathway. Both BRG1 and GLMP might serve as therapeutic targets for disorders associated with dysregulated lipid metabolism, such as NAFLD and NAFLD-associated HCC.